Acute abdominal pain in a 13-year-old female adolescent - Monteiro Cunha, Sara (2021)
Introduction: Ovarian torsion can occur at any pediatric age, mainly between the ages of 9 and 14 years. Diagnosis is challenging, as symptoms are nonspecific, misleading to other more common diagnoses, as genitourinary and gastrointestinal disorders. In children, ovarian lesions leading to torsion are typically benign and cystic. Surgical approach is safe, as most cases of early torsed ovary untwisting exhibit later normal ovarian function. Case report: A 13-year-old female adolescent was referred to the Emergency Department for vomiting, left low back pain, and diffuse abdominal pain with irradiation to the hypogastric area, associated with urinary symptoms. Abdomen was tender in the right iliac fossa and hypogastric area. Analytical study revealed increased inflammatory parameters, urinary test strip was negative, and pelvic computed tomography showed a cystic lesion of ovarian origin. Due to suspicion of cyst torsion, laparoscopic surgery was performed, revealing a necrotic adnexal torsion requiring adnexectomy. Discussion: Although often suspected, adnexal torsion is rarely confirmed. Although ovarian torsion accounts for a small number of all gynecological emergencies, it represents a common diagnostic challenge in the emergency setting. Conclusion: As ovary viability depends on early diagnosis, a high index of suspicion is required. This clinical case raises awareness of this entity in the differential diagnosis of lower abdominal pain in female children and adolescents.